The Shining Path: love, madness, and revolution in the Andes - Starn, Orin (W.W. Norton & Company, 2019)
The train to Machu Picchu -- A tree can be a weapon -- Comrade Norah -- The great rupture -- First blood -- The lynching -- Inquest in the Andes -- Shouting in the rocks -- The Queen of Villa -- The shining trench -- The Party Congress -- The death of Comrade Norah -- The revolution comes to Villa -- A fish out of water -- Ghostbusters -- The clever frog -- The birthday party -- A death foretold -- The wolf and the whale -- Fat cheeks, affirmative! -- The silence of the lambs.